Expert Oracle - Kyte, Thomas (Apress, 2012)
The inspiration for the material contained in this book comes from my experiences developing Oracle software and working with fellow Oracle developers, helping them build reliable and robust applications based on the Oracle database. The book is basically a reflection of what I do everyday and of the issues I see people encountering each and every day. I covered what I felt was most relevant – namely the Oracle database and its architecture. I could have written a similarly-titled book explaining how to develop an application using a specific language and architecture – for example, one using Java Server Pages that speak to Enterprise Java Beans, that use JDBC to communicate with Oracle. However, at the end of the day, you really do need to understand the topics covered here in order to build such an application successfully. This book deals with what I believe needs to be universally known to develop successfully with Oracle, whether you are a Visual Basic programmer using ODBC, a Java programmer using EJBs and JDBC, or a Perl programmer using DBI Perl. This book does not promote any specific application architecture; it does not compare 3-tier to client-server. Rather, it covers what the database can do and what you must understand about the way it works. Since the database is at the heart of any application architecture, the book should have a broad audience.